Frequency of Adverse Reaction in Antenatal Booked Patients of a Tertiary Care Centre Receiving Intravenous Iron Isomaltoside - Sidra Khaliid, Farah Deeba Nasrullah, Riffat Jaleel, Farah Shabih-Ul-Hasnain (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the frequency of adverse reaction in antenatal patients of Civil Hospital Karachi receiving intravenous iron isomaltoside for the treatment of iron deficiency anaemia. Methodology: A six months cross sectional study was undertaken at the department of Obstetrics & Gynaecology Civil Hospital Karachi. In this study women who weighted < 75 kg at the time of presentation to the antenatal clinic received 1000 mg parenteral iron isomaltoside infusion. Women with body weight ≥ 75 kg on the same occasion received 1500 mg parenteral iron during a minimum infusion of 30 min, diluted in 100–500 ml of saline. The patients who received parenteral iron were kept under observation in a secluded quiet room and directed to lie on her back on a comfortable bed. The researcher monitored the patient during and thirty minutes after the end of infusion to assess the adverse reactions. Results: The mean age of the women was 27.2 + 4 years, mean gestational age was 36 + 4 weeks. Out of 276 women, 17 (6%) experienced the adverse reactions. Majority (>94%) developed mild reaction which did not require any treatment. The adverse effects were significantly associated with younger age <30 years (p value .03), gestational age < 36 weeks (p value .001), use of tobacco (p value .001), hypertension (p value .001) and diabetes (p value .001) Conclusion: Findings of the study concludes that the use of a single high-dose infusion (up to 1500 mg) of paranteral iron (isomaltoside) during pregnancy is effective and safe for treating IDA in this population. Keywords: Adverse reaction, antenatal booked patients, Intravenous iron isomaltoside